2023
DOI: 10.4236/as.2023.149081
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Pan-Sharpening Algorithms to Access an Agriculture Area: A Mississippi Case Study

Reginald S. Fletcher

Abstract: Numerous satellites collect imagery of the Earth's surface daily, providing information to the public and private sectors. The fusion (pan-sharpening) of high-resolution panchromatic satellite imagery with lower-resolution multispectral satellite imagery has shown promise for monitoring natural resources and farming areas. It results in new imagery with more detail than the original multispectral or panchromatic images. In agricultural areas in Mississippi, landscapes can range from complex mixtures of vegetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…It demonstrates its universal nature and suitability for sharpening images captured by various sensors recording in bands outside the visible range. Notably, Fletcher (2023), utilising WordView 3 farmland images, demonstrated that applying this method to convert 1.2 m spectral channels to 0.3 m resolution yielded some of the best results among the 17 pansharpening methods tested. The slight blurring observed in satellite images sharpened using the HCS technique diminishes with increasing geometric resolution.…”
Section: Geometric and Radiometric Correlation Of Remote Sensing Datamentioning
confidence: 99%
“…It demonstrates its universal nature and suitability for sharpening images captured by various sensors recording in bands outside the visible range. Notably, Fletcher (2023), utilising WordView 3 farmland images, demonstrated that applying this method to convert 1.2 m spectral channels to 0.3 m resolution yielded some of the best results among the 17 pansharpening methods tested. The slight blurring observed in satellite images sharpened using the HCS technique diminishes with increasing geometric resolution.…”
Section: Geometric and Radiometric Correlation Of Remote Sensing Datamentioning
confidence: 99%
“…In this case we are dealing with a low-quality fused image, which differs significantly from the MS orthophotomosaic. All the above limits may, as mentioned above, be modified but in any case, the index values should be less than three in order for a fused image to be characterized in terms of its quality and/or used for classification [63,[71][72][73][74][75][76][77][78][79][80][81][82][83][84].…”
Section: Fused Image Production Process and Control Of Thematic Infor...mentioning
confidence: 99%